2021
DOI: 10.3390/antiox10060951
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Coreopsis lanceolata Flower Extract against Oxidative Stress-Induced Apoptosis in Neuronal Cells and Mice

Abstract: (1) Background: Coreopsis lanceolata L. is a perennial plant of the family Asteraceae, and its flower is known to contain flavonoids with various bioactivities. We evaluated the effect of Coreopsis lanceolata L. flower (CLF) extracts on H2O2-induced oxidative stress (OS) in neuronal cells and mouse neurons. (2) Methods: The flowering part of CL was used as CLF1 (70% ethanol extract) and CLF2 (water extract), and 10 types of phenolic compounds were quantified using high-performance liquid chromatography. To eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Moreover, ROS can induce mitochondrial dysfunction, which is crucial for DA neurons of the SNc since they require more ATP to maintain resting membrane potential, propagate action potentials, and achieve synaptic transmission [9,54]. Reducing ROS has always been a potential treatment for PD [55,56]. In the present study, we investigated the antioxidant effect of VB12 in multiple PD models.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, ROS can induce mitochondrial dysfunction, which is crucial for DA neurons of the SNc since they require more ATP to maintain resting membrane potential, propagate action potentials, and achieve synaptic transmission [9,54]. Reducing ROS has always been a potential treatment for PD [55,56]. In the present study, we investigated the antioxidant effect of VB12 in multiple PD models.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, JAC4 increased the ATP content and ∆Ψm as a result of the suppression of mitochondrial damage. ROS reduction has been used as a treatment strategy for PD [42,43]. In this study, it was demonstrated that JAC4 improves mitochondrial damage and represses ROS production.…”
Section: Discussionmentioning
confidence: 89%
“…In the in-vitro study, CLF also enhanced the expression of the Bcl-xL protein but reduced the expression of Bax and the cleavage of caspase-3. Thus, CLF ameliorated oxidative stress and protected neurons from MPTP/MPP+-induced apoptosis 28 .…”
Section: Coreopsis Lanceolatementioning
confidence: 92%